2014
DOI: 10.1002/hep.27289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of purified eicosapentaenoic and docosahexaenoic acids in nonalcoholic fatty liver disease: Results from the WELCOME* study

Abstract: on behalf of the WELCOME Study InvestigatorsThere is no licensed treatment for nonalcoholic fatty liver disease (NAFLD), a condition that increases risk of chronic liver disease, type 2 diabetes, and cardiovascular disease. We tested whether 15-18 months of treatment with docosahexaenoic acid (DHA) plus eicosapentaenoic acid (EPA; Omacor/Lovaza, 4 g/day) decreased liver fat and improved two histologically validated liver fibrosis biomarker scores (primary outcomes). Patients with NAFLD were randomized in a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
237
4
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 281 publications
(258 citation statements)
references
References 36 publications
(69 reference statements)
10
237
4
7
Order By: Relevance
“…Consort diagram and the baseline characteristics of both placebo and active groups have been reported previously (5). All participants had NAFLD and features of metabolic syndrome.…”
Section: Subjects and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consort diagram and the baseline characteristics of both placebo and active groups have been reported previously (5). All participants had NAFLD and features of metabolic syndrome.…”
Section: Subjects and Measurementsmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acid (PUFA) treatment (3) and weight loss (4) can be effective in decreasing liver fat and also triglyceride concentrations. Recently in patients with NAFLD we have suggested that the omega-3 fatty acid docosahexaenoic acid (DHA, 22:6n-3) may be more effective that the omega-3 fatty acid eicosapentanoic acid (EPA; 20:5n-3) in decreasing liver fat (5). In this randomised placebo-controlled trial that tested the effects of high dose purified omega-3 fatty acids, we showed an association between high levels of erythrocyte DHA, but not EPA, enrichment and decreased liver fat.…”
Section: Introductionmentioning
confidence: 99%
“…In a phase 2 double-blind, randomized, placebo-controlled trial, treatment with low-dosage (1800 mg/day) or high-dosage (2700 mg/day) ethyl-eicosapentanoic acid for 12 months had no significant effects on the histologic features of NASH 137 . In contrast, others have shown a benefit of n-3 PUFA treatment on liver fat assessed by magnetic resonance imaging (and have suggested that a greater benefit in NAFLD was associated with docosahexanoic acid treatment) [138][139][140] . Additionally, it has been suggested that the PNPLA3 148MM may attenuate any beneficial effect conferred by n-3 PUFA treatment in NAFLD 141 , emphasizing that future clinical trials testing new potential treatments for NAFLD should also perhaps consider the influence of different genotypes to modify any treatment effect.…”
Section: Management and Treatment Options For Nafldmentioning
confidence: 93%
“…94,95 Role of lipid-lowering drugs in NAFLD is inconclusive. While there is some data suggesting improvement in NASH with statins, 96 99 While there are few available treatment options of proven efficacy in NAFLD, promising drugs are under development and under evaluation for regulatory approval.…”
Section: (3) Other Drugsmentioning
confidence: 99%